The meat paradox and health-related aspects: A cluster analysis among red meat consumers - Riccardo Testa; Giuseppina Rizzo; Riccardo Vecchio; Francesco Vella; Giorgio Schifani; Giuseppina Migliore (Food Quality and Preference, 2025)

Cost-effectiveness of conventional and precision agriculture sprayers in Southern Italian vineyards: A break-even point analysis - Riccardo Testa; Antonino Galati; Giorgio Schifani; Giuseppina Migliore (Precision Agriculture, 2025)
Through targeted spray applications, precision agriculture can provide not only environmental benefits but also lower production costs, improving farm competitiveness. Nevertheless, few studies have focused on the cost-effectiveness of precision agriculture sprayers in vineyards, which are among the most widespread specialty crops. Therefore, this is the first study that aims to evaluate the cost-effectiveness of variable rate technology (VRT) and unmanned aerial vehicle (UAV) sprayers compared to a conventional sprayer in a hypothetical and representative vineyard area of southern Italy. The economic analysis, based on technological parameters in the literature, enabled the identification of the minimum farm size (break-even point) for introducing precision agriculture sprayers (PAS), considering the annual cost of the pesticide treatments (equipment and pesticide costs). Our findings revealed that the UAV sprayer—if permitted by law—could be the most convenient option for farms larger than 2.27 ha, whereas the VRT sprayer should be chosen by farms over 17.02 ha. However, public subsidies, such as those provided by the Italian Recovery Plan, make adopting VRT sprayers also economically viable for areas as small as 3.03 ha. Finally, the sensitivity analysis confirmed that the purchase price and pesticide cost are the most sensitive parameters affecting the break-even points. Our findings shed light on the economic sustainability of these innovative sprayers, a key driver for their adoption by farmers and for setting future strategies for facing the current agricultural crisis.

What drives and obstacles the intention to purchase green skincare products? A study of the Italian market of green skincare products - Riccardo Testa; Francesco Vella; Giuseppina Rizzo; Giorgio Schifani; Giuseppina Migliore (Journal of Cleaner Production, 2024)

Understanding the consumption of plant-based meat alternatives and the role of health-related aspects. A study of the Italian market - Giuseppina Rizzo; Riccardo Testa; Emilia Cubero Dudinskaya; Serena Mandolesi; Francesco Solfanelli; Raffaele Zanoli; Giorgio Schifani; Giuseppina Migliore (International Journal of Gastronomy and Food Science, 2023)

Soil Erosion Mitigation by Perennial Species Under Mediterranean Environment - Salvatore Luciano Cosentino; Venera Copani; Giovanni Scalici; Danilo Scordia; Giorgio Testa (BioEnergy Research, 2015)

Long-Term Yields of Switchgrass, Giant Reed, and Miscanthus in the Mediterranean Basin - Efthymia Alexopoulou; Federica Zanetti; Danilo Scordia; Walter Zegada-Lizarazu; Myrsini Christou; Giorgio Testa; Salvatore L. Cosentino; Andrea Monti (BioEnergy Research, 2015)

Evaluation of DRB1 high resolution typing by a new SSO-based Luminex method - Manuela Testi; Sandra Iannelli; Giuseppe Testa; Maria Troiano; Simonetta Capelli; Fiorenza Fruet; Giorgio Federici; Andrea Bontadini; Marco Andreani (Molecular Biology Reports, 2012)